VD_FINDINFO HC / 2012 / 43 vom 24. November 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, PROLONGATION DU BAIL À LOYER, ANNULABILITÉ, RÉSILIATION, RÉSILIATION ABUSIVE | 271 CO, 271a CO, 272b CO, 273 CO